Performance evaluation on error probabilities of coded BPSK system using the Linear (23, 12) Golay code with hard-decision decoding - Syed Abdullah, Sharifah Sakeenah; Khalifa, Othman Omran; Abdul Rahman, Farah; Nasir, Haidawati (IEEE, 2019)
Channel impairment due to the existence of noise and interference is a major problem in the communication system. To combat this problem, channel coding technique is often used. In this paper, Bit Error Rate (BER) performance is evaluated by a simulation in a MATLAB program using the linear (23,12) Golay Code with coded BPSK system for the fading channel. The performance of the coded Binary-Phase Shift Keying (BPSK) is investigated. It is shown that the performance of coded signal in terms of BER is better than the uncoded signal in this study. However, the main focus is to compare the BER of linear (23,12) Golay Code using linear and cyclic code techniques with coded BPSK in hard decision. The simulation results show that the linear code has a better performance of BER compared to the cyclic code.